Performance Analysis Of Vertical Type Mangosteen Skin Pressing Machine - Ningsih Ningsih; Suwati Suwati; Rosyid Ridho (Universitas Muhammadiyah Mataram, 2021)
This study aims to determine the working mechanism of the vertical type mangosteen peel penepung machine, to determine the production capacity of the results of the performance analysis of the vertical type mangosteen peel penepung machine, to determine the electrical power requirements and to determine the efficiency of the machine the results of the performance analysis of the vertical type mangosteen peel penepung machine. The method used in this research is the Experimental method by conducting experiments in the Agricultural Workshop Lab. The design used is a Completely Randomised Design consisting of 3 treatments using a vertical type mangosteen peel penepung machine with load variations, namely, P1 = 50 grams, P2 = 100 grams, P3 = 150 grams using a 1400 rpm rotation. Each treatment was repeated 3 times so as to get 9 experimental units. The research data were analysed using load variations (Anova table) at the 5% level and if there was a treatment that had a significant effect, further tests were carried out using the Real Differential Test (BNJ) at the 5% real level. The results of the analysis and research show that the working mechanism of the machine uses an electric motor as a driving force, the highest mangosteen skin pressing capacity in P3 is 177.80 grams / second and the lowest in P1 80.82 grams / second, the use of the highest electrical power requirements in P3 0.17 watts and the lowest electrical power usage P1 is 0.09 watts and the efficiency of the machine in P1, P2 and P3 is the same at 53.33%.